The Effect of Low-Molecular-Weight Heparin on Immune Balance of Patients with Repeated Implantation Failure During the Implantation Window: Heparin in Patients with Repeated Implantation Failure - Li, Qiuping; Zhang, Yun; Zou, Lian (Cellular and Molecular Biology, 2023)
This study investigates the effect of low-molecular-weight heparin (LMWH) on cytokines TNF-α, IFN-γ, IL-2, IL-4, IL-6, and IL-10 in peripheral blood of patients with repeated implantation failure during the implantation window. From May 2019 to March 2021, we enrolled 32 patients with recurrent implantation failure (RIF group) and 30 patients with successful pregnancy after the first frozen embryo transfer (control group) in the Reproductive Medicine Centre of Wuxi Maternity and Child Health Care Hospital. During the implantation window, the following features were compared between two groups and between different time points using ELISA: the status of immune cytokines in peripheral blood; Th1 cytokines (TNF-α, IFN-γ, and IL-2) and Th2 cytokines (IL-4, IL-6, and IL-10) in peripheral blood. The levels of Th1 cytokines in the RIF group before treatment were higher in comparison with the control group. In the RIF group, the LMWH treatment can inhibit the expression of Th1 cytokines and enhance the expression of Th2 cytokines. Using LMWH during the implantation window can improve the immune imbalance of patients with repeated implantation failure, which makes it a potential treatment strategy for patients with abnormal cellular immunity.